1992
DOI: 10.1108/09649429210011336
|View full text |Cite
|
Sign up to set email alerts
|

Academic Attainment, Assimilation and Feminism in Canadian Schools of Business

Abstract: Investigates employment discrimination in Canadian Schools of Business. A review of Statistics Canada data on student (1971, 1978) and faculty composition (1980, 1985, 1989) demonstrates that the number of females as a percentage of undergraduate and graduate students of business has increased significantly as has the total percentage of female faculty. Females are, however, significantly under‐represented in senior academic positions of associate and full professors with little change over the study period. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…While Adam Smith's theories may work in the field of accountancy, this is not the experience in academe or business and industry. Orser (1992) finds that while close to half of current undergraduate and graduate students in Canadian schools of business are female, only 17 percent of full-time faculty are women and they are clustered at the lower levels of the academic ladder. Likewise, Allen (1991) notes that, while women have made gains from 1985 to 1990 in attaining management positions overall, they are still somewhat underrepresented at the middle levels and substantially underrepresented at the senior levels in Canadian corporations.…”
Section: Alternativesmentioning
confidence: 99%
“…While Adam Smith's theories may work in the field of accountancy, this is not the experience in academe or business and industry. Orser (1992) finds that while close to half of current undergraduate and graduate students in Canadian schools of business are female, only 17 percent of full-time faculty are women and they are clustered at the lower levels of the academic ladder. Likewise, Allen (1991) notes that, while women have made gains from 1985 to 1990 in attaining management positions overall, they are still somewhat underrepresented at the middle levels and substantially underrepresented at the senior levels in Canadian corporations.…”
Section: Alternativesmentioning
confidence: 99%
“…However, there has been no fundamental change. In spite of the inflow of women into the world of science, curriculum changes have been slow (Evans 1995;Schuster and Van Dyne 1985), the gender imbalance in scholarship has remained (Winnifred and Hamilton 1988) as well as the marked sex inequality at the higher levels of academic hierarchies (see for example , Acker 1994;Foster 1994;Martin 1994;Orser 1992;Robbins and Kahn 1985;Stolte-Heiskanen 1991). We feel that to be able to offer insights into why this is so, instead of studying open gender discrimination we must now turn to the more discrete modes of discrimination taking place in our work communities.…”
mentioning
confidence: 99%
“…37 Additionally, Orser has concluded that "an absence of women in senior academic positions contributes to biased research and funding, weakens the tenure review process, and contributes to the lack of feminist research in the administrative sciences." 38 Moreover, the results of this study have important implications for academic administrators. Many institutions periodically evaluate salary differentials between male and female faculty; however, a more extensive investigation would involve efforts to expose the possible existence of an academic glass ceiling.…”
Section: Discussionmentioning
confidence: 94%